Feeling right is feeling good: psychological well-being and emotional fit with culture in autonomy- versus relatedness-promoting situations - De Leersnyder, Jozefien; Kim, Heejung; Mesquita, Batja (Frontiers in Psychology, 2015)
The current research tested the idea that it is the cultural fit of emotions, rather than certain emotions per se, that predicts psychological well-being. We reasoned that emotional fit in the domains of life that afford the realization of central cultural mandates would be particularly important to psychological well-being. We tested this hypothesis with samples from three cultural contexts that are known to differ with respect to their main cultural mandates: a European American (N = 30), a Korean (N = 80), and a Belgian sample (N = 266). Cultural fit was measured by comparing an individual’s patterns of emotions to the average cultural pattern for the same type of situation on the Emotional Patterns Questionnaire (De Leersnyder et al., 2011). Consistent with our hypothesis, we found evidence for “universality without uniformity”: in each sample, psychological well-being was associated with emotional fit in the domain that was key to the cultural mandate. However, cultures varied with regard to the particular domain involved. Psychological well-being was predicted by emotional fit (a) in autonomy-promoting situations at work in the U.S., (b) in relatedness-promoting situations at home in Korea, and (c) in both autonomy-promoting and relatedness-promoting situations in Belgium. These findings show that the experience of culturally appropriate patterns of emotions contributes to psychological well-being. One interpretation is that experiencing appropriate emotions is itself a realization of the cultural mandates.